THE EVALUATION OF THE QUALITY OF SANITATION AND STORED WATER FOR DOMESTIC USE IN THE UMLAZI P SECTION INFORMAL SETTLEMENT IN SOUTH AFRICA. - Shangase, Simangaliso; TS Ndlovu, P Pillay (Student's Journal of Health Research Africa, 2024)
Background South Africa is faced with a struggle to manage the supply of water due to growing informal settlements where infrastructure is limited resulting in the contamination of water during collection and storage. The researcher aims to determine the level of knowledge and awareness of water contamination and the safety of water in terms of microbial and chemical content. Aim: This study aimed to investigate the quality of stored water and the handling of storage vessels for domestic use at the informal settlement of the Umlazi P Section, in the south-west of Durban. The study objectives: The objectives of the study were to determine the knowledge and awareness of water contamination using a questionnaire and investigate the exposure of water to microbial agents due to poor hygiene and storage. To test stored water samples for pathogenic organisms as well as compliance with the South African Water Quality Guidelines for domestic use. Methodology Data collection entailed the administration of a questionnaire to 269 participants, including the laboratory analysis of water samples collected from water storage containers used in each household. Results A positive total coliform count was found among 13 (5%) households in the study of 269 households rendering their drinking water a high risk for domestic use despite only accounting for 5% of the population. The remaining 256 showed to have a negligible exposure to waterborne contamination. The Escherichia coli was not detected making drinking water acceptable in terms of fecal coliform bacteria. Conclusion The data collected from the study showed that poor hygienic practices and infrastructure were at the center of water contamination. Recommendations The study recommended infrastructure development, hygiene monitoring tools, and cost-effective water treatment products.